Fibrolamellar hepatocellular carcinoma in ascitic fluid: A case report with cytohistological correlation. Issue 9 (24th May 2016) - Bernieh, Anas; Adams, Kristen; Susan Liu, Xuehui; Flowers, Rhyne; Shenoy, Veena; Baliga, Mithra; Akhtar, Israh
Abstract : The fibrolamellar variant of hepatocellular carcinoma (FL‐HCC) is distinguished from other hepatocellular carcinoma's (HCC) by its unique clinical and pathological features. Cytological features of this tumor on fine needle aspiration have been described earlier. We report a rare case of a 17‐year‐old African American male with metastatic FL‐HCC, diagnosed by body fluid cytology. The patient presented with ascites and computed tomography (CT) scan revealed multiple omental masses and liver lesions. The fluid sample was obtained along with the omental biopsy and was found positive for metastatic fibrolamellar hepatocellular carcinoma. The fluid cytology showed atypical polygonal cells with enlarged nuclei, prominent nucleoli, and abundant granular cytoplasm. Cytomorphologic features of FL‐HCC presenting in body fluids have been rarely described before. This case enriches the cytopathology literature by providing awareness of this tumor presenting as metastasis in body fluids, especially in young individuals with liver lesions. Presence of a concurrent biopsy specimen provided cytohistological correlation, as it remains the gold standard for the accuracy and reliability of cytological diagnoses. Diagn. Cytopathol. 2016;44:757–760. © 2016 Wiley Periodicals, Inc.